Reinterpreting al-Faḍlu al-Ḥawāʾij Through the Lens of Maqāṣid al Sharīʿah: Zakat Practices Among Employees at UIN Suska Riau - Zulkifli, Zulkifli; Gemilang, Kemas Muhammad; Almaktsur, Mohammad Abdi; Andrini , Rozi; Fitrianto, Fitrianto (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
The concept of al-faḍlu al-ḥawāʾij in zakat jurisprudence distinguishes between essential needs (ḥājat aṣliyyah) and surplus wealth that forms the basis of zakat obligations. In contemporary socio-economic contexts, however, the increasing diversity of living standards and professional needs has made the determination of surplus wealth more complex. At UIN Sultan Syarif Kasim Riau, differing interpretations of al-faḍlu al-ḥawāʾij among employees have contributed to the less-than-optimal implementation of institutional zakat policies administered through the UPZ BAZNAS. Although many employees, particularly civil servants in Class IV, Echelon II structural officials, and lecturers holding senior functional positions receive relatively high incomes, the assessment and institutional distribution of income-based zakat remain inconsistent. This study employs a qualitative approach within a normative-empirical paradigm, combining an analysis of classical and contemporary fiqh literature with field data obtained through in-depth interviews and document analysis. The findings reveal that employees tend to interpret a “decent standard of living” broadly, encompassing not only basic necessities but also assets such as private vehicles, relatively spacious housing, professional expenditures related to research and community service, and long-term financial investments. Through reinterpretation based on the framework of maqāṣid al-sharīʿah, the study argues that al-faḍlu al-ḥawāʾij should be understood as wealth remaining after the fulfillment of primary (ḍarūriyyāt) and certain secondary (ḥājiyyāt) needs that support the preservation of religion, life, intellect, lineage, and wealth. Establishing measurable and context-sensitive standards of basic needs is therefore essential for determining income-based zakat obligations more equitably and for strengthening institutional zakat management, including the consideration of salary-based deductions derived from actual surplus income.